Application of contrast-enhanced ultrasound for extradigital glomus tumor in the thigh: a case report - Dai, Guangyuan; Fang, Jiawen; Zhang, Shengmin (Frontiers in Oncology, 2025)
Glomus tumors (GTs) are rare neoplasms, classically presenting as subungual lesions with pathognomonic triad of severe paroxysmal pain triggered by cold, pressure, or touch. Extradigital glomus tumors (EGTs) pose significant diagnostic challenges due to their anatomical atypicality and frequently ambiguous clinical manifestations. Ultrasonography remains the primary imaging modality for evaluating soft tissue masses. In the diagnostic assessment of GTs by sonographers, the identification predominantly relies on characteristic clinical presentations combined with the demonstration of intratumoral hypervascularity through color Doppler imaging, as grayscale ultrasound features exhibit nonspecific characteristics. However, conventional ultrasonography encounters significant diagnostic challenges in EGTs with atypical clinical presentations and deep-seated locations, primarily due to the markedly reduced sensitivity of color Doppler in assessing blood flow within deep soft tissue lesions. In contrast, contrast-enhanced ultrasound (CEUS) allows dynamic visualization of microvascular perfusion patterns, enabling precise evaluation of intratumoral hemodynamic characteristics. This technique may assist in enhancing diagnostic accuracy and guiding targeted biopsies. We report a case of a 56-year-old man with a 4-year history of drug-resistant left thigh pain. CEUS revealed a 21-mm intramuscular mass exhibiting rapid heterogeneous enhancement followed by rapid washout, suggesting hypervascularity. Histopathology confirmed a glomus tumor of uncertain malignant potential. This case highlights the clinical and imaging characteristics of EGTs, providing clinicians with a comprehensive understanding of this rare entity.